Evaluation of NxTAG Respiratory Pathogen Panel and Comparison with xTAG Respiratory Viral Panel Fast v2 and Film Array Respiratory Panel for Detecting Respiratory Pathogens in Nasopharyngeal Aspirates and Swine/Avian-Origin Influenza A Subtypes in Culture Isolates - K. H. Chan; K. K. W. To; P. T. W. Li; T. L. Wong; R. Zhang; K. K. H. Chik; G. Chan; C. C. Y. Yip; H. L. Chen; I. F. N. Hung; J. F. W. Chan; K. Y. Yuen (Advances in Virology)
This study evaluated a new multiplex kit, Luminex NxTAG Respiratory Pathogen Panel, for respiratory pathogens and compared it with xTAG RVP Fast v2 and FilmArray Respiratory Panel using nasopharyngeal aspirate specimens and culture isolates of different swine/avian-origin influenza A subtypes (H2N2, H5N1, H7N9, H5N6, and H9N2). NxTAG RPP gave sensitivity of 95.2%, specificity of 99.6%, PPV of 93.5%, and NPV of 99.7%. NxTAG RPP, xTAG RVP, and FilmArray RP had highly concordant performance among each other for the detection of respiratory pathogens. The mean analytic sensitivity (TCID50/ml) of NxTAG RPP, xTAG RVP, and FilmArray RP for detection of swine/avian-origin influenza A subtype isolates was 0.7, 41.8, and 0.8, respectively. All three multiplex assays correctly typed and genotyped the influenza viruses, except for NxTAG RRP that could not distinguish H3N2 from H3N2v. Further investigation should be performed if H3N2v is suspected to be the cause of disease. Sensitive and specific laboratory diagnosis of all influenza A viruses subtypes is especially essential in certain epidemic regions, such as Southeast Asia. The results of this study should help clinical laboratory professionals to be aware of the different performances of commercially available molecular multiplex RT-PCR assays that are commonly adopted in many clinical diagnostic laboratories.